Relationship between age at menarche and breast cancer in individuals, as well as in first-degree kin and estrogen receptor status: a Mendelian randomization study - Zhao, Zhijun; Zhang, Jinming; Tian, Xiaofeng (Frontiers in Oncology, 2024)
Target We executed a Mendelian randomization (MR) investigation employing two distinct cohorts of genetic instrumental variables to elucidate the causal nexus between age at menarche (AAM) and the incidence of disparate breast cancer (BC) subtypes, in addition to the incidence of BC among first-degree kin. Methods We aggregated statistical data pertaining to AAM and BC from various consortia representing a homogenous population cohort. MR analysis was conducted employing inverse variance weighted (IVW) methodology as the principal approach, complemented by weighted median and MR-Egger regression techniques for an exhaustive evaluation. To evaluate the presence of pleiotropy, we applied the MR-Egger intercept test, MR-PRESSO, and leave-one-out sensitivity analysis. Results Upon exclusion of confounding SNP, an increment of one standard deviation in AAM was inversely correlated with the incidence of BC. (odds ratio [OR] 0.896, 95% confidence interval [CI] 0.831–0.968)/(OR 0.998, 95% CI 0.996–0.999) and estrogen receptor-positive (ER+) BC incidence (OR 0.895, 95% CI 0.814–0.983). It was also associated with reducing the risk of maternal BC incidence (OR 0.995, 95% CI 0.990–0.999) and sibling BC incidence (OR 0.997, 95% CI 0.994–0.999). No significant association was found between AAM and estrogen receptor-negative (ER-) BC incidence (OR 0.936, 95% CI 0.845–1.037). Conclusion Our study substantiated the causal relationship between a delayed AAM and a diminished risk of BC in probands, as well as in their maternal progenitors and siblings. Furthermore, the analysis suggests that AAM exerts a considerable potential causal influence on the risk of developing Luminal-a/b subtype of BC.